Estimation of the demand for palliative care in a hospital in southern Peru - Brayan Miranda-Chavez; Pablo Carrillo Barriga; Javier Flores-Cohaila; Marco Rivarola Hidalgo; Alvaro Taype-Rondan (PLoS ONE, 2025)
Objective To estimate the need for palliative care in deceased patients at the Daniel Alcides Carrión Hospital (Tacna, Peru) during 2023. Methodology An analytical cross-sectional study was conducted with data from adult patients who died in a Peruvian hospital in 2023. Data were collected through the review of death certificates and medical records using the EsSalud Intelligent Health Service. Two methods were used to estimate the need for palliative care: the Rosenwax method (medium estimation) and the Murtagh method (medium-high estimation). Results Out of 255 deaths, 239 were analyzed. The median age was 76 years. 58.2% had two or more comorbidities, and only 3.8% had received palliative care previously. According to the Murtagh method, 82.9% of the patients required palliative care, while the Rosenwax method estimated a need of 74.1%. The most common diagnoses requiring palliative care were: neoplasms (33.5%), chronic obstructive pulmonary disease (15.1%), and renal disease (11.3%). An association was found between having two or more comorbidities and a greater need for palliative care. Conclusion It was found that between 7 and 8 out of every 10 patients needed palliative care, an estimate higher than in other regions. Additionally, having two or more comorbidities was associated with the need for these services. These findings highlight the urgent need for palliative care services in Peru, suggesting that their proper implementation is crucial for improving end-of-life care.